2017
DOI: 10.1021/jacs.6b11124
|View full text |Cite
|
Sign up to set email alerts
|

Constant Volume Gate-Opening by Freezing Rotational Dynamics in Microporous Organically Pillared Layered Silicates

Abstract: Microporous organically pillared layered silicates (MOPS) are a class of microporous hybrid materials that, by varying pillar density, allows for optimization of guest recognition without the need to explore different framework topologies. MOPS are found to be capable of discriminating two very similar gases, carbon dioxide and acetylene, by selective gate-opening solely through quenching pillar dynamics. Contrary to conventional gate-opening in metal organic frameworks, the additional adsorption capacity is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 35 publications
(66 reference statements)
0
42
0
Order By: Relevance
“…The volume expansion in the adsorbent solid is disadvantageous as it may damage the storage tank, decompose the moldings, and also may result in slower diffusion of gases in the tank. Consequently, design of new porous materials that can show abrupt guest adsorption and desorption without significant volume change is highly desirable …”
Section: Figurementioning
confidence: 99%
“…The volume expansion in the adsorbent solid is disadvantageous as it may damage the storage tank, decompose the moldings, and also may result in slower diffusion of gases in the tank. Consequently, design of new porous materials that can show abrupt guest adsorption and desorption without significant volume change is highly desirable …”
Section: Figurementioning
confidence: 99%
“…In conventional gate‐opening, the additional adsorption capacity is associated with macroscopic volume changes exerting significant mechanical stress on the framework. By contrast, we showed that MOPS are able of discriminating two very similar gases (CO 2 and C 2 H 2 ) by a new fully reversible and selective gate‐opening at constant volume which is triggered solely by freezing pillar dynamics without any macroscopic displacements of the framework (Figure ) . The underlying mechanism was unraveled by in situ physisorption/X‐ray diffraction in combination with 13 C solid‐state NMR spectroscopy.…”
Section: Structural Dynamism In Mopsmentioning
confidence: 88%
“…Prior to gate‐opening, CO 2 is adsorbed in a pseudohexagonal packing in the voids between three adjacent pillars. At gate‐opening pressure CO 2 is capable to squeeze into the gaps along the pseudohexagonal a ‐axis, which are too small for CO 2 with rotating pillars, concomitantly blocking the rotation of the pillars (Figure ) . According to the classification of Schneemann et al.…”
Section: Structural Dynamism In Mopsmentioning
confidence: 99%
See 2 more Smart Citations